Juri Lotman on proper name - Pärli, Ülle; Rudakovskaja, Eleonora (Sign Systems Studies, 2002)
The article treats the concept of proper name in Juri Lotman’s semiotics, taking into account also studies in the same field by other authors of the Tartu-Moscow school (V. Ivanov, B. Ogibenin, V. Toporov, B. Uspenski). Focus is laid at three sub-topics: name and myth, name and text, name and artistic creation. One of the sources of treating proper name for both the program article by J. Lotman and B. Uspenski (“Myth — Name — Culture”), and works by several other semioticians of the Tartu–Moscow school is confidence in the connection between proper name and mythical (a-semiotic) thought: semiosis equals here with nomination. Proper name plurality, different re-namings affirm the continuing importance of mythical thinking in later culture. Proper names (such as personal names, place names) belong, in addition to natural language, also into a certain individual system, forming thus an interlinguistic layer located on the boundary of language. J. Lotman stresses that art has a specific power of uniting general and proper name (proper name characterized here by individuality, explosiveness). An artistic work is even doubly of proper name character: both the act of creation and its reception are by nature individual and unrepeated. In the opinion of the authors the treatment of proper name by the Tartu-Moscow school contains fruitful and promising standpoints for the analysis of contemporary culture that, however, have been applied unjustifiably little.